The application of geostatistical ore reserve evaluation methods in Archaean gold deposits: a case study of the woodbine deposit, Agnes mine in the Barberton area - Brooker, Andrew John (My University, 2016)
The object of this project report is to examine how geostatistical methods can be applied to ore reserve evaluations in the Archaean gold deposits of the Barberton area, supported by a case study of the Woodbine deposit. Examilally there were two main problems identified when trying to evaluate an Archaean gold deposit; firstly, the presence of extreme values within the sampling data and secondly, the absence of a clear geological contacts between which the occurrence of gold is limited. In examining the first of these problems, a number of geostatistical evaluation methods were examined in the light of their influence on extreme values within the sampling data. Three methods were examined in this project report. The second of the two problems is that of estimating the total gold content (grammes) within a block of ore when the gold mineralisation occurs over a width, is greater than the expected mining width. The approach adopted was to optimise the sampling data to various likely mining widths, thereby creating a number of data sets. one for each optimised stops width. The kriging of the optimised data allowed for the development of a Grade-Stope Width model for each "block", whereby the actual stope values could be compared to,the block estimates generated by various geostatistical methods under consideration. This concept of a Grade-Stope Width model in a "wide reef" has important ramifications to Block Factor calculations.[Abbreviated Abstract. Open document to view full version]
A project report submitted to the Faculty of Engineering, University of the Witwatersrand. Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Engineering. Johannesburg, 1991.